Protective Microglial Subset in Development, Aging, and Disease: Lessons From Transcriptomic Studies - Benmamar-Badel, Anouk; Owens, Trevor; Wlodarczyk, Agnieszka (Frontiers in Immunology, 2020)
Microglial heterogeneity has been the topic of much discussion in the scientific community. Elucidation of their plasticity and adaptability to disease states triggered early efforts to characterize microglial subsets. Over time, their phenotypes, and later on their homeostatic signature, were revealed, through use of increasingly advanced transcriptomic techniques. Recently, an increasing number of these “microglial signatures” have been reported in various homeostatic and disease contexts. Remarkably, many of these states show similar overlapping microglial gene expression patterns, both in homeostasis and in disease or injury. In this review, we integrate information from these studies, and we propose a unique subset, for which we introduce a core signature, based on our own research and reports from the literature. We describe that this subset is found in development and in normal aging as well as in diverse diseases. We discuss the functions of this subset as well as how it is induced.